Saussurean Strukturalism on Motherhood in Gibran’s ‘ummi’ poem - 'Aqil Dlabit 'Alimuddin Putra Zulfah; Mustari Mustari; Farrel Izham Prayitno (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
his study investigates Kahlil Gibran’s poem Ummi by applying Ferdinand de Saussure’s structuralist framework to explore its multifaceted portrayal of motherhood. The research problem arises from the limited scholarly attention to structuralist readings of modern Arabic poetry, particularly in revealing how linguistic and symbolic systems shape thematic depth. The study aims to examine how linguistic signs and natural symbols construct the maternal figure as both a universal and cultural archetype, and to assess the broader significance of structuralist analysis in modern literary studies. Methodologically, the research employs a descriptive-analytical approach within a qualitative paradigm. Through close reading and structural analysis, the study identifies the ways in which syntagmatic and paradigmatic relations, along with binary oppositions, contribute to the cohesion and resonance of the poem. The results demonstrate that key linguistic signs—such as the Arabic word أمي (“my mother”)—alongside natural images like the sun, earth, trees, and flowers, function as semiotic units that elevate the mother beyond her biological role. These symbols present her as an embodiment of affection, resilience, and protection, while binary oppositions such as strength versus weakness and hope versus despair enhance the poem’s philosophical dimensions. The study contributes to literary scholarship by showing that structuralist analysis not only uncovers the symbolic depth of Gibran’s poetry but also situates motherhood as a cultural and cosmic principle. Ultimately, this research reinforces the continued relevance of Saussurean theory in interpreting Arabic literature and enriches critical perspectives on Gibran’s poetic vision.